PENGARUH OPINI AUDIT, AUDIT TENURE DAN REPUTASI AUDITOR TERHADAP AUDIT REPORT LAG - Ega Radytyas Yasmine; Nurhayati (Jurnal Nusa Akuntansi, 2026)
Audit report lag refers to the time gap between the end of the fiscal year and the issuance date of the audit report, reflecting the efficiency and timeliness of the audit process. A prolonged audit report lag may indicate obstacles in the audit process, such as financial statement complexity, communication quality between auditor and client, and other external factors. This condition can reduce the relevance and reliability of financial information for stakeholders.This study aims to analyze the influence of audit opinion, audit tenure, and auditor reputation on audit report lag in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Audit opinion reflects the auditor’s assessment of the fairness of financial statements, audit tenure indicates the duration of the auditor-client relationship, while auditor reputation refers to the credibility and public recognition of the auditing firm.The research employs a quantitative method with an associative approach. The results show that audit opinion and audit tenure have a significant effect on audit report lag, while auditor reputation does not have a significant effect. These findings provide important implications for auditors, company management, and regulators in improving audit efficiency and enhancing financial reporting transparency.